2015
DOI: 10.1007/s00253-015-6666-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparative scale purification of fucosyl-N-acetylglucosamine disaccharides and their evaluation as potential prebiotics and antiadhesins

Abstract: Fucosyl-N-acetylglucosamine disaccharides are important core structures that form part of human mucosal and milk glyco-complexes. We have previously shown that AlfB and AlfC α-L-fucosidases from Lactobacillus casei are able to synthesize fucosyl-α-1,3--N-acetylglucosamine (Fuc-α1,3-GlcNAc) and fucosyl-α-1,6-N-acetylglucosamine (Fuc-α1,6-GlcNAc), respectively, in transglycosylation reactions. Here, these reactions were performed in a semipreparative scale, and the produced disaccharides were purified. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 55 publications
1
35
0
2
Order By: Relevance
“…Analytical and semipreparative HPLC analyses. Transfucosylation reaction products were purified by high-performance liquid chromatography (HPLC) using a preparative Rezex RCM-monosaccharide column (Phenomenex) as previously described (65). Appropriate fractions were pooled, concentrated, and analyzed by using an analytical Rezex RSO-oligosaccharide column (Phenomenex) in the case of 6=FN-Asn synthesis and an analytical Rezex RCM-monosaccharide column (Phenomenex) in the case of N2F N-glycan, 6=FucGal, and 6=FucGlc synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Analytical and semipreparative HPLC analyses. Transfucosylation reaction products were purified by high-performance liquid chromatography (HPLC) using a preparative Rezex RCM-monosaccharide column (Phenomenex) as previously described (65). Appropriate fractions were pooled, concentrated, and analyzed by using an analytical Rezex RSO-oligosaccharide column (Phenomenex) in the case of 6=FN-Asn synthesis and an analytical Rezex RCM-monosaccharide column (Phenomenex) in the case of N2F N-glycan, 6=FucGal, and 6=FucGlc synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…Positive probiotic effects of Lactobacillus species have been shown on immune system stimulation, atopic disease, and several types of diarrhea in children among others (Ashraf and Shah 2014;Kalliomaki et al 2003;Pedone et al 2000;Rodriguez-Diaz and Monedero 2013;Szajewska et al 2013). We have previously demonstrated that fucosyl-Nacetylglucosamine disaccharides, that form part of HMOs and also part of glyco-complexes from the mucosa, were fermented by strains of L. casei, L. rhamnosus, B. breve, and B. pseudocatenulatum (Becerra et al 2015), suggesting a potential prebiotic effect for those carbohydrates. Additionally, we have characterized in L. casei strain BL23 the gnb operon (gnbREFGBCDA) that is involved in the transport and catabolism of LNB and GNB (Bidart et al 2014).…”
Section: Introductionmentioning
confidence: 90%
“…The transgalactosylation reaction products were analyzed and purified by HPLC (Jasco PU2080Plus system) using analytical and preparative Rezex RCM-Monosaccharide columns (Phenomenex, Torrance, CA, USA), respectively, as described previously (Becerra et al 2015). Di-and monosaccharides were confirmed by comparison of their retention times with those of standards (LNB, GNB, galactose, GlcNAc, and GalNAc).…”
Section: Analytical and Semi-preparative Hplc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…los distintos disacáridos que forman parte de oligosacáridos más complejos. Se ha analizado el potencial inmunomodulador de la LNB y GNB sintetizadas aquí, y de los fucosil-N-acetilglucosamina disacáridos, Fuc1-3 y Fuc1-6, sintetizados previamente en nuestro laboratorio (Becerra et al, 2015;Rodriguez-Diaz et al, 2013). Para los ensayos de análisis del potencial inmunomodulador se utilizaron dos modelos descritos en la sección de materiales y métodos, el de incubación de los disacáridos con la línea celular de epitelio intestinal HT-29 en co-cultivo con células mononucleares de sangre periférica (PBMC) en placas transwell, y el de incubación directa de los disacáridos con PBMC.…”
Section: Análisis Del Potencial Inmunomodulador De La Lnb Gnbunclassified